For this case we have the following expression:
[tex]\sqrt [4] {11} \sqrt [4] {10}[/tex]
For radical properties, we have to:
[tex]\sqrt [a] {b} \sqrt [a] {c} = \sqrt [a] {bc}[/tex]
Therefore, making use of the definition, we can rewrite the given expression.
We have then:
[tex]\sqrt [4] {11} \sqrt [4] {10} = \sqrt [4] {(11) (10)}\\\sqrt [4] {11} \sqrt [4] {10} = \sqrt [4] {110}[/tex]
Answer:
The equivalent expression is given by:
[tex]\sqrt [4] {11} \sqrt [4] {10} = \sqrt [4] {110}[/tex]
Option D